A grounded theory of female adolescents' dating experiences and factors influencing safety: the dynamics of the Circle - Toscano Sharyl E (BMC, 2007)
Abstract Background This paper describes the nature and characteristics of the dating relationships of adolescent females, including any of their experiences of abuse. Methods A grounded theory approach was used with 22 theoretically sampled female adolescents ages 15-18. Results Several important themes emerged: Seven stages of dating consistently described the relationships of female adolescents. A circle consisting of two interacting same sex peer groups provided structure for each teen as they navigated the dating course. The circle was the central factor affecting a female adolescent's potential for risk or harm in dating relationships. Teens defined abuse as an act where the intention is to hurt. Having once succumbed to sexual pressure, teens felt unable to refuse sex in subsequent situations. Conclusion An awareness of both the stages of dating and the dynamics of the circle will assist health care providers to plan and implement interventions in the female adolescent population. Study findings on factors and influences that support non-abusive versus abusive relationship might help identify female teens at risk and/or support interventions aimed at preventing dating violence.